Development and initial testing of a tailored telephone intervention delivered by peers to prevent recurring opioid-overdoses (TTIP-PRO). Issue 2 (17th March 2016) - Winhusen, T.; Theobald, J.; Lewis, D.; Wilder, C. M.; Lyons, M. S.
Abstract: Individuals with opioid use disorder experiencing a non-fatal opioid-overdose (OOD) are at heightened risk for future OODs; there are no interventions to facilitate treatment enrollment for these patients. Our goal was to develop and initially test the 'tailored telephone intervention delivered by peers to prevent recurring opioid-overdoses' (TTIP-PRO), a computer-facilitated, peer-delivered, individually tailored secondary prevention intervention designed to: (i) encourage patients to initiate medication-assisted treatment (MAT) and (ii) increase OOD knowledge. A pre–post-study assessed TTIP-PRO-content acceptability and software performance. Two Peer Interventionists, who were abstinent from illicit opioids, enrolled in MAT and had experience with OOD, were recruited from a MAT clinic. Recruitment letters were sent to patients treated for OOD in a hospital emergency department within the prior 8 months. Eight patients received TTIP-PRO and completed pre-/post-assessment. Peer Interventionists completed training within 4 h and reported high satisfaction with TTIP-PRO. There were no performance issues with the software. All participants rated TTIP-PRO as 'very helpful'. Participants' OOD knowledge increased significantly, with 69.9% correct responses pre-TTIP-PRO and 93.6% post-TTIP-PRO. Interest in receiving MAT, measured on a 10-point scale, increased from 8.1 to 9.5, but this change was not statistically significant. Further development and testing of TTIP-PRO appears warranted.